ANALYSIS OF MANAGEMENT AND REGIONAL APPARATUS ORGANIZATIONS IN KUTAI KARTANEGARA REGENCY BASED ON GOVERNMENT REGULATION NUMBER 18 OF 2016 ON REGIONAL APPARATUS - Insyori, Nuzul Wahyu (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
ABSTRACT. This study originates from the issue of a lack of in-depth and specific evaluation to assess the implementation of Government Regulation No. 18 of 2016, which has significant implications for organizational changes in regencies/cities across Indonesia. The study aims to analyze the management and organization of regional apparatus in Kutai Kartanegara Regency based on Government Regulation No. 18 of 2016 concerning Regional Apparatus, utilizing G.R. Terry's management theory. The research employs a qualitative study method with a descriptive analysis approach. Data were collected through observations, interviews, and document analysis. In this analysis, G.R. Terry's management theory serves as the foundation for understanding fundamental management concepts, such as planning, organizing, leading, directing, and controlling. The findings reveal that the implementation of Government Regulation No. 18 of 2016 has influenced various aspects of management and the organization of regional apparatus in Kutai Kartanegara Regency. Terry emphasizes the importance of sound planning, efficient organizational structures, strong leadership, clear direction, and strict control to achieve organizational objectives. By analyzing the management and organizational practices of regional apparatus through this theoretical lens, the study provides deeper insights into how management concepts can be applied within the context of local government administration. The conclusion of the study underscores the importance of applying effective management principles to improve the performance and efficiency of local government operations. Recommendations based on the findings include expanding training and development for regional apparatus staff, enhancing collaboration between work units, and improving performance control and evaluation systems. Key words: Organization and Management: Regional Apparatus; Kutai Kartanegara; Government Number 18 of 2016; IPDN.